Adakah Hubungan Kekerasan Fisik dan Verbal Orang Tua dengan Perkembangan Psikososial Anak Usia Sekolah? - Livana PH; M. Ramli; Carolina Ligya Radjah (Jurnal Ilmu Keperawatan Jiwa, 2021)
Violence in children is an action taken by the caregiver or parent in physical or verbal forms that can endanger the child's health, survival, dignity and development of the child and one of them is psychosocial development. The child's psychosocial development will be disrupted if the caregiver or parent is wrong in educating the child, so that the child withdraws, has difficulty concentrating, likes to interfere, and shows behavior that is not appropriate to his age stage. This study aims to determine the relationship between physical and verbal abuse of parents and the psychosocial development of school age children. This quantitative study used a cross sectional approach with a descriptive correlational design. The study population was school-age children living in Kendal City. The sample consisted of 55 respondents. The data were collected using a questionnaire consisting of 3 statements, namely 8 statements of physical violence, 8 statements of verbal violence and 16 statements of psychosocial development. The validity test was carried out on 30 respondents with r count> 0.361. Reliability test results obtained Cronbach alpha 0.917.Statistical test using the chi square test. The results showed that there was a relationship between the physical and verbal abuse of parents and the psychosocial development of school age children with a value of p = 0.000 (p value <0.05).